CYBER ENTERPRENEURIAL INTENTION MAHASISWA FAKULTAS KEGURUAN DAN ILMU PENDIDIKAN UNIVERSITAS SEBELAS MARET - Tiffany Aprillia; Susilaningsih Susilaningsih; Nurhasan Hamidi (Jurnal Pengembangan Pendidikan Akuntansi dan Keuangan (JPPAK), 2023)
ABSTRACT This study aims to identify what factors determine cyber entrepreneurial intentions of students of the Faculty of Teacher Training and Education, Sebelas Maret University. This research is a quantitative research with a correlational approach. The population in this study were students of the Accounting Education Study Program, Economic Education and Office Administration Education Class of 2019-2021. The sample were 258 students, taken from the population using Proportionate Stratified Random Sampling techniques. The data collection technique used in this study was a questionnaire to measure cyber entrepreneurial intentions of students of the Faculty of Teacher Training and Education, Sebelas Maret University. The data analysis technique used exploratory factor analysis. The results of research on determinants of students cyber entrepreneurial intentions found two new factors, including (1) self potential factors (45.509%) including digital knowledge, social media support, social support, personal attitudes, entrepreneurial education, entrepreneurial spirit, self efficacy, the need for achievement, and self-perception creativity; (2) perception factors (9.544%) include entrepreneurial role models, social background, perceived ease of use, and perceived expediency. Keyword: eksploratory factor analysis, entrepreneurship, cyber entrepreneurial intention, entrepreneurial education ABSTRAK Penelitian ini bertujuan untuk mengidentifikasi faktor apa saja yang menentukan cyber entrepreneurial intention mahasiswa Fakultas Keguruan dan Ilmu Pendidikan Universitas Sebelas Maret. Penelitian ini merupakan penelitian kuantitatif dengan pendekatan korelasional. Populasi penelitian ini adalah mahasiswa Program Studi Pendidikan Akuntansi, Pendidikan Ekonomi dan Pendidikan Administrasi Perkantoran Angkatan 2019-2021. Sampel yang diambil dari populasi penelitian adalah sejumlah 258 mahasiswa dengan menggunakan Teknik proportionate stratified random sampling. Teknik pengambilan data yang digunakan dalam penelitian ini menggunakan angket yang digunakan untuk mengukur cyber entrepreneurial intention mahasiswa Fakultas Keguruan dan Ilmu Pendidikan Universitas Sebelas Maret. Teknik analisis data menggunakan analisis faktor eksploratory. Hasil penelitian terhadap cyber entrepreneurial intention mahasiswa didapatkan dua faktor baru antara lain (1) faktor potensi diri (45,509%) meliputi pengetahuan digital, dukungan media sosial, dukungan sosial, sikap pribadi, pendidikan kewirausahaan, semangat kewirausahaan, self efficacy, kebutuhan untuk berprestasi, dan kreativitas persepsi diri; (2) faktor persepsi (9,544%) meliputi role model kewirausahaan, latar belakang sosial, persepsi kemudahan penggunaan, dan persepsi kemanfaatan. Kata Kunci: analisis faktor eksploratory, kewirausahaan, cyber entrepreneurial intention, pendidikan kewirausahaan